Caractéristiques de l’évolution spatio-temporelle de Thaumatotibia leucotreta Meyrick (Lepidoptera : Tortricidae) dans les zones de production cotonnière de Côte d’Ivoire - Ochou, Germain Elisabeth Cynthia; Kobenan, Koffi Christophe; Dekoula, Charles Sekpa; Kone, Pitou Woklin Euloge; Didi, Roland; Kouakou, Malanno; Bini, Kouadio Kra Norbert; Mamadou, Dagnogo; Dick, Acka Emmanuel; Ochou, Ochou Germain (European Scientific Journal, ESJ, 2018)
In order to update knowledge on the spatio-temporal evolution of Thaumatotibia leucotreta, the geographical areas and seasons of predilection of adult and larval populations have been studied in the last six years from 2012 to 2017. Monitoring of natural adult populations revealed that populations were more abundant in the southern cotton production area as compared to the north. A Monitoring of larval infestations showed that infestations occurred on cotton at the end of august (0.10 larvae/100 bolls) and increased gradually during october-november (0.31 to 0.93 larvae/100 bolls), indicating a strong relationship between evolution of adult and larval populations and cotton phenology. Early sowings exhibited higher infestation levels (0.87 larvae/100 bolls). Annual variations of pest infestation levels increased from years to years, from 0.23 to 0.49 larvae/100 bolls over the study period. Mapping the geographic distribution of infestations showed highest pest densities in the southern zone, mostly in surrounding areas of Boron (1.52 larvae/100 bolls). With regard to the emerging status of T. leucotreta over recent years, the current pyrethroid resistance management strategy deserves to be improved on the basis of the pest geographic and seasonal profiles.